Patterns in northern stream guilds and communities - Muotka, Timo (1994)
Patterns in northern stream communities are not yet well understood. Here, I document spatial patterns in predator-prey relationships and patterns in community structure of semi-sessile stream insects and stream bryophytes in northeastern Finland. Spatial distribution of predatory stoneflies was generally random, whereas caddisfly predators (Rhyacophila spp.) were aggregated to areas of highest density of larval black flies. After the emergence of black flies, the distribution of R. obliterata became random. The analysis of mapped point patterns proved more robust in detecting scales of predator-prey interaction than more conventional sampling techniques. Ontogenetic niche shifts in the microhabitat use by filter-feeding caddis larvae were detected in all five species studied. In particular, 5th instar larvae were clearly separated from the younger larval stages, irrespective of species. Ontogenetic niche shifts are probably nearly universal among benthic insects, and should be considered in any study of lotic insect community structure. It is further suggested that coexistence in the guild of filter-feeding caddis larvae is facilitated by independent aggregation of species to patchily distributed resources. Occurrence of stream bryophytes was strongly associated with the disturbance history (substratum movement, water level fluctuation) of a site. In the absence of disturbance, a few tall perennials (e.g. Fontinalis spp.), were able to monopolize space. Frequently disturbed habitats in large rivers were characterized by low-statured shuttle species, which either possess a high capacity for propagule dispersal or are able to withstand frequent scouring of substratum. In streams, small-scale disturbances leave patches open for colonization by facultatively aquatic species which tolerate both submersed and stranded conditions.